Functional polymer coatings : principles, methods and applications - Wu, Limin; Baghdachi, Jamil (Hoboken, New Jersey : John Wiley & Sons Inc., 2015)
Focusing on a variety of coatings, this book provides detailed discussion on preparation, novel techniques, recent developments, and design theories to present the advantages of each function and provide the tools for better product performance and properties. -'' 'Presents advantages and benefits of properties and applications of the novel' coating types -'' 'Includes chapters on specific and novel coatings, like nanocomposite, surface wettability tunable, stimuli-responsive, anti-fouling, antibacterial, self-healing, and structural coloring -'' 'Provides detailed discussion on recent developments in the field as well as current and future perspectives -'' 'Acts as a guide for polymer and materials researchers in optimizing polymer coating properties and increasing product performance.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Coating processes; Plastic coating; Polymers -- Industrial applications; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Coating processes; Plastic coating; Polymers -- Industrial applications; Electronic books; Electronic books